Cutting-Edge Technologies for Renewable Energy Production and Storage - Prussi, Matteo (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Anthropogenic greenhouse gas (GHG) emissions are dramatically influencing the environment, and research is strongly committed to proposing alternatives, mainly based on renewable energy sources. Low GHG electricity production from renewables is well established but issues of grid balancing are limiting their application. Energy storage is a key topic for the further deployment of renewable energy production. Besides batteries and other types of electrical storage, electrofuels and bioderived fuels may offer suitable alternatives in some specific scenarios. This Special Issue includes contributions on the energy conversion technologies and use, energy storage, technologies integration, e-fuels, and pilot and large-scale applications.